STRATEGI PENINGKATAN MUTU PENDIDIKAN ISLAM - Rozi, M. Asep Fathur (EDUKASI: Jurnal Pendidikan Islam, 2016)
The development of human resources influenced the quality of educational institutions.The quality of educational institutions influenced by vision and mission the agency. The formulation of vision and mission institutions involving stakeholders already set by the institutions. A factor causing the quality of education not been successful among others, strategy education is input oriented and management of education has been is macro-oriented. After the preparation of vision and mission, institutions formulate strategic plan. Strategy is important policy of the as the basis of in making institutional program. Business could be undertaken by educational institutions to improve the quality of institutions, among other: prepared leader who quality, formulate vision and mission with a characteristic wholly owned by intitusi, formulate strategy in an effort to create the purpose of institutions, improve the ability of human resources, conducted a survey market, furnish facilities and infrastructure, financial management, to improve cooperation with the stakeholders, tending consistency quality.Pengembangan sumberdaya manusia dipengaruhi kualitas lembaga pendidikan. Kualitas lembaga pendidikan dipengaruhi oleh visi dan misi lembaga tersebut. Perumusan visi dan misi lembaga melibatkan stakeholder yang sudah di tentukan oleh lembaga. Faktor yang meny ebabkan mutu pendidikan kurang berhasil antara lain, strategi pendidikan yang bersifat input oriented dan pengelolaan pendidikan selama ini lebih bersifat macro-oriented. Setelah penyusunan visi dan misi, lembaga merumuskan rencana strategis. Strategi merupakan kebijakan penting dari lembaga sebagai patokan dalam pembuatan program kelembagaan. Usaha yang bisa dilakukan oleh lembaga pendidikan untuk meningkatkan mutu institusi, antara lain: menyiapkan pemimpin yang berkualitas, merumuskan visi dan misi dengan ciri khas yang hanya dimiliki oleh intitusi, merumuskan strategi dalam rangka mewujudkan tujuan institusi, meningkatkan kemampuan sumberdaya manusia, melakukan survei pasar, melengkapi sarana dan prasarana, manajemen keuangan, menjalin kerjasama dengan stakeholder, merawat konsistensi mutu.